Strategi Pengelolaan Lahan Sebagai Upaya Optimalisasi Produksi Tanaman Hortikultura di Kecamatan Samarinda Utara: Land Management Strategies for Optimizing Horticultural Crop Production in North Samarinda District (Jurnal Ecosolum, 2025)
The strategic role of the agricultural sector in Samarinda City, particularly in North Samarinda District, supports food security and the regional economy. North Samarinda District holds a crucial position as an agricultural buffer zone in Samarinda, but in the past five years, there has been a significant decrease in horticultural production, such as tomatoes from 1,467.9 tons in 2021 to 263 tons in 2024, chilies from 236.2 tons to 129.9 tons, and shallots from 7.5 tons in 2022 to 1.1 tons in 2023. Various challenges, including climate change, land degradation, and urbanization, have contributed to a decline in agricultural productivity. This study aims to evaluate land suitability to optimize horticultural crop production in the region. The research method employed is a land suitability analysis using a Geographic Information System (GIS) approach, which identifies biophysical factors such as soil texture, pH, and soil depth, as well as soil sampling for further analysis. The results show that most of the land in North Samarinda District has S3 (marginally suitable) land suitability for shallots, chilies, and tomatoes. The suitability class for S3 is influenced by limiting factors such as rainfall, soil pH, erosion, and slope. Further discussion reveals that technical improvements, such as fertilization, the addition of organic matter, and terrace construction, can enhance land suitability. Through appropriate technical improvements, land suitability can be upgraded to class S2 (moderately suitable), which in practice will support increased horticultural yields and strengthen food security in North Samarinda.
Keywords: Land Suitability; GIS; Agricultural Productivity; North Samarinda; Horticultural Crops